¿Nuevo imperio, viejo patio trasero? Los Estados Unidos, América Latina y la guerra en Irak - Heine, Jorge (Estudios Internacionales, 2003)
Although the purpose of this article is to examine the position of Latin America in relation to the war with Iraq, and its significance for the development of inter-American relations, the case of Chile and its refusal to support the invasion of Iraq is illustrative of many of the Latin American dilemmas and challenges. The "Iraqi question" is interesting from an analytical point of view because it raises the confrontation between the application of a new doctrine, in this case that of "preventive war", and what ended up being, for most Latin American countries, the defense - unfruitful, by the way - of what could be considered the old norms of the international system. After the war, this allows us to analyze many of the arguments raised and evaluate to what extent the decisions taken corresponded or not to the most permanent interests of the States of the region.